2019
DOI: 10.1016/j.jid.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Imiquimod-Induced Psoriasis in Mice Depends on the IL-17 Signaling of Keratinocytes

Abstract: The pathology of psoriasis strongly depends on IL-17A. Monoclonal antibodies blocking either the cytokine or its receptor are among the most efficient treatments for psoriatic patients. Keratinocytes can be activated upon exposure to IL-17A and tumor necrosis factor-a and secrete secondary cytokines and chemokines in the inflamed skin. In psoriasis and its imiquimod-induced mouse model, a strong skin infiltration of neutrophils and inflammatory monocytes can be observed. However, to date, it is not clear how e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(99 citation statements)
references
References 32 publications
1
87
0
4
Order By: Relevance
“…In a similar way, the role of the cytoskeleton regulator Arp2/3 complex was evaluated by transcriptomics of an Arpc4 knockout mouse strain to investigate psoriasis-specific features [207]. In the field of psoriasis research, Imiquimod (IMQ)-induced dermatitis is a widely used murine model which mainly acts via TLR7/8 agonism [208] and largely depends on IL-17 signaling [209][210][211]. Swindell et al investigated its validity in a large study with different mouse strains and gender dependency and compared transcriptomic data with psoriasis and other human inflammatory skin disease profiles.…”
Section: Validating Disease Modelsmentioning
confidence: 99%
“…In a similar way, the role of the cytoskeleton regulator Arp2/3 complex was evaluated by transcriptomics of an Arpc4 knockout mouse strain to investigate psoriasis-specific features [207]. In the field of psoriasis research, Imiquimod (IMQ)-induced dermatitis is a widely used murine model which mainly acts via TLR7/8 agonism [208] and largely depends on IL-17 signaling [209][210][211]. Swindell et al investigated its validity in a large study with different mouse strains and gender dependency and compared transcriptomic data with psoriasis and other human inflammatory skin disease profiles.…”
Section: Validating Disease Modelsmentioning
confidence: 99%
“…Psoriasis can be conceptualized as an exaggerated physiological response to epithelial damage or wounding, and we now know that keratinocytes are essential and central players in this response (Figure 1). Like most informative studies, the results reported by Moos et al (2019) allow for speculations and suggest new questions. Could a future therapeutic strategy aim to neutralize IL-17 signaling selectively in keratinocytes?…”
mentioning
confidence: 64%
“…One of the best described types of T cell-mediated inflammation leading to a chronic inflammatory skin disease is type 17 immune-driven induction of psoriasis. Moos and colleagues (2019) now provide convincing evidence that this inflammatory cascade is critically dependent on keratinocytes (Moos et al, 2019). Moos and colleagues (2019) investigated several murine models in which the IL-17 receptor component IL-17RA was deleted in distinct cell types, including T cells, neutrophils, macrophages, or keratinocytes, to determine which cell types were critical IL-17 responders in skin.…”
mentioning
confidence: 99%
“…In psoriasis, IL-1 is likely to initiate the in ammatory response and cause dysfunction of keratinocytes; furthermore, TNF-α, IL-1 and IL-6 derived from dysregulated keratinocytes amplify the in ammatory response through promoting the differentiation of myeloid dendritic cells [19,25,26]. IL-17A and IL-22 released by activated lymphocytes mediate chronic in ammation in psoriasis [21,[27][28][29]. In psoriasis, high expression of COX2 is associated with a persistent in ammatory response [19,30].…”
Section: Discussionmentioning
confidence: 99%